Mashup Man. - Leone, Raechal (American Journalism Review)
This article focuses on Adrian Holovaty, who became a celebrity among online journalists for his work fusing colorful maps with crime statistics for the Web site Chicagocrime.org. He was awarded the 2005 Batten Award for Innovations in Journalism for the site. Holovaty has an exalted status in the computer geek world of mashups, which are places on the Web where databases and computer graphics are "mashed" together in innovative, sophisticated and user-friendly ways. Holovaty's background is a blend of computer programming and journalism. He is said to have amazing foresight for where the future of journalism might be headed. He is editor of editorial innovations at Newsweek Interactive.